The Effect of Mind Mapping Model on The Students of Biology Learning Outcomes of SMAN 12 Maros - Amalia, Fitri; Khaeriyah, Khaeriyah; Nur, Rizki Amalia (Journal of Biological Science and Education, 2021)
This research is an experimental study that aims to determine the differences in the learning outcomes of class XI students of SMA Negeri 12 Maros who are taught using the Mind Mapping learning model and the conventional model on the Excretion System Principal Material. The sample in this study were students of class XI MIA 1 and class XI MIA 2 SMA Negeri 12 Maros. The experimental class was taught using a mind mapping model, while the control class was taught using a conventional model. Based on the results of data analysis obtained a sig value of 0.001 0.05, it can be concluded that there is an influence on student learning outcomes using the mind mapping learning model in class XI SMA Negeri 12 Maros.